Odpoczynek Boga (Rdz 2,1-3) w interpretacji Ojców Kościoła - Czyżewski, Bogdan (Vox Patrum, 2014)
The theme of this paper is the exegesis of Gen 2:1-3 in selected writings of the Church Fathers and early Christian writers. The Early Church authors pondered over the passage in question, seeking to find the meaning of God’s resting on the seventh day from all his work of creation of the world and man. In their statements, early Christian writers clearly stated that the Biblical text should be read spiritually while treated as a metaphor. For God does not need rest, but man. It is for man that the Creator made the Sabbath day, and made it holy, and since the Resurrection of Christ, Sunday has been a holy day designated for rest and celebration. Concurrently, it was the announcement of the eighth day, or eternity, in which a man, free from all the trouble and bodily decay, will forever rest in God and live a true union with Him.